Utilization of Chamilo LMS in Learning Media Courses as an Effort to Digitalize Education - Nasir, Agus; Nasrum, Akbar; Haeniah, Nurul (International Journal of Business, Law, and Education, 2023)
The number of online learning platforms available for free makes it easier for lecturers to deliver teaching materials but difficult for students. The use of different LMS by each lecturer causes almost all LMS on students' mobile devices. In order to make the learning process easier to organize, educational institutions should have one LMS that is the choice to be used together. Only now, Universitas Sembilanbelas November Kolaka has no LMS, especially the Indonesian Language Education study program. Therefore, this research will produce a Learning Management System that can support online learning systems synchronously, asynchronously, and mixed learning in the Indonesian Language Education study program at Universitas Sembilanbelas November Kolaka. The LMS that will be created is open-source-based so that it can be developed according to user needs. Specifically, the subjects included in the system are Educational media subjects at the college level. However, this LMS will be developed into a Faculty LMS that can be used to support learning management in all study programs. Five interrelated stages are needed to develop this LMS: Analysis, Design, Development, Implementation, and Evaluation. These development stages are known as the ADDIE model. An LMS meets the standard criteria for use in Learning Media courses through these stages. The resulting prototype is very useful for learning management, so its use can be expanded and developed to improve learning management within the faculty.